Effectiveness and safety of different anaesthetic techniques consideration for laparoscopic tenckhoff catheter insertion in esrf patients from year 2018 to 2021 - Mujiman, Nurthaqifah Farhani (2023)
Background The general perception of laparoscopic procedure necessitates general anaesthesia (GA) hindered the successful initiation of continuous ambulatory peritoneal dialysis (CAPD) in Malaysia. End-stage renal failure (ESRF) patients possess complex multiple co-morbidities that put them under higher mortality and morbidity with GA. In this study, we will investigate the safety and efficacy of different anaesthetic considerations for laparoscopic tenckhoff catheter insertion. Material and Method The retrospective study included 523 patients who underwent elective laparoscopic tenckhoff catheter insertion in Hospital Selayang for four years between 1 January 2018 and 31 December 2021. The patients received either monitored anaesthesia care (MAC), subarachnoid block (SAB), or SAB+MAC. Their intraoperative haemodynamic parameters like systolic blood pressure (SBP) and heart rate (HR) were recorded. Any haemodynamic fluctuations (hypotension and desaturation) and postoperative nausea and vomiting (PONV) were collected. Results The distribution of anaesthesia was 36.52% under SAB, 41.68% under MAC, and 22.75% under SAB+MAC. No significant differences were observed in haemodynamic (SBP+HR) changes at the time taken among all three groups. However, SAB+MAC and SAB group required boluses of vasopressor intraoperatively more than the MAC group (22.7% vs. 14.7% vs. 9.2%, p=0.003). Otherwise, there was no significant difference in PONV and desaturations among the three groups. Conclusions Laparoscopic tenckhoff catheter insertion is feasible to be done in different modes of anaesthesia other than GA. It accommodates many successful tenckhoff insertions and facilitates CAPD initiation without compromising patients' safety and comfort.